2015
DOI: 10.1007/s12603-015-0539-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin intake on cognitive decline in older adults: Evaluation of the evidence

Abstract: Evaluation of the totality of the currently available evidence indicates that intake of the above vitamins, either as a monotherapy, or in combination with other vitamins, has no clinically-relevant effect on delaying cognitive decline or delaying the onset of dementia in older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…In line with this indication, recent neuropathological, post-mortem studies showed that γ-T concentrations were associated with lower amyloid load and neurofibrillary tangle severity, whereas high α-T was associated with lower amyloid levels only when γ-T levels were high, thus concluding that randomized trials should consider the contribution of γ-T [176]. More recently, two systematic reviews of randomized controlled trials investigating the effect of nutritional interventions on cognitive performance in older non-demented adults found no convincing evidence for clinically-relevant effects of vitamin E (either as a monotherapy or in combination with other antioxidant vitamins such as vitamin C or β-carotene) on delaying cognitive decline or the onset of dementia [177,178]. Moreover, a multi-site, randomized, double-blind controlled clinical trial recruiting adults with Down syndrome older than 50 years, with participants assigned to receive 1000 IU of vitamin E orally twice daily for 3 years or identical placebo, failed to show any effects of vitamin E in slowing the progression of cognitive deterioration [179].…”
Section: α-Tocopherol Synaptic Plasticity and Cognitive Functionsmentioning
confidence: 99%
“…In line with this indication, recent neuropathological, post-mortem studies showed that γ-T concentrations were associated with lower amyloid load and neurofibrillary tangle severity, whereas high α-T was associated with lower amyloid levels only when γ-T levels were high, thus concluding that randomized trials should consider the contribution of γ-T [176]. More recently, two systematic reviews of randomized controlled trials investigating the effect of nutritional interventions on cognitive performance in older non-demented adults found no convincing evidence for clinically-relevant effects of vitamin E (either as a monotherapy or in combination with other antioxidant vitamins such as vitamin C or β-carotene) on delaying cognitive decline or the onset of dementia [177,178]. Moreover, a multi-site, randomized, double-blind controlled clinical trial recruiting adults with Down syndrome older than 50 years, with participants assigned to receive 1000 IU of vitamin E orally twice daily for 3 years or identical placebo, failed to show any effects of vitamin E in slowing the progression of cognitive deterioration [179].…”
Section: α-Tocopherol Synaptic Plasticity and Cognitive Functionsmentioning
confidence: 99%
“…Studies investigating healthy, non-deficient adults showed contradicting results, though (for review, e.g., Malouf and Grimley Evans, 2006 ; Reay et al, 2013 ). While some authors did not report any effects of vitamin B6 on cognitive performance, others showed a positive correlation even in healthy older adults (Deijen et al, 1992 ; Kado et al, 2005 ; Balk et al, 2007 ; Harris et al, 2015 ; Krause and Roupas, 2015 ). Interestingly, Harris et al ( 2015 ) reported a dissociation of vitamin supplementation effects in healthy older adults: while blood levels could be improved, no effect on cognitive performance was found.…”
Section: Discussionmentioning
confidence: 99%
“…The review considered studies that included primary outcome measures from a range of cognitive function tests, brain imaging techniques, blood biomarkers of MCI and AD risk as previously described [5,6] Types of studies The review considered published systematic reviews and meta-analyses on the listed dietary components.…”
Section: Types Of Outcomesmentioning
confidence: 99%
“…Data extracted from papers included details of the populations, interventions, study methods, and outcomes of significance to the question of this review article and specific objectives. The data were extracted and listed by intervention and levels of evidence using the National Health and Medical Research Council (NHMRC, Australia) criteria [8] as previously described [5]. While studies were categorized by study design, it should be emphasized that this does not automatically translate to the strength of the evidence, due to other contributing factors that were also assessed.…”
Section: Data Extraction and Synthesismentioning
confidence: 99%